2021
DOI: 10.1016/j.bja.2021.01.029
|View full text |Cite
|
Sign up to set email alerts
|

First genome-wide association study on rocuronium dose requirements shows association with SLCO1A2

Abstract: Background: Rocuronium, a common neuromuscular blocking agent, is mainly excreted unchanged in urine (10e25%) and bile (>70%). Age, sex, liver blood flow, smoking, medical conditions, and ethnic background can affect its pharmacological actions. However, reasons for the wide variation in rocuronium requirements are mostly unknown. We hypothesised that pharmacogenetic factors might explain part of the variation. Methods: One thousand women undergoing surgery for breast cancer were studied. Anaesthesia was maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…20,21 Single-nucleotide polymorphisms in the organic anion transporting polypeptide (OATP) family have also been identified as a potential source of variability in rocuronium dose requirements, as rocuronium is a known substrate of OATP1A2 and allelic frequency appears to vary by race. [22][23][24] Interestingly, TOF monitoring was also found to be associated with the need for additional reversal. We felt, however, this is likely related to a selection bias because clinicians who are concerned that, either they may have given too much relaxant or have not had adequate time for the relaxant to wear off, may be more likely to apply a qualitative TOF monitor to attempt to assess depth of neuromuscular blockade and further reassure themselves that the patient is in a good position to be reversed with neostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Single-nucleotide polymorphisms in the organic anion transporting polypeptide (OATP) family have also been identified as a potential source of variability in rocuronium dose requirements, as rocuronium is a known substrate of OATP1A2 and allelic frequency appears to vary by race. [22][23][24] Interestingly, TOF monitoring was also found to be associated with the need for additional reversal. We felt, however, this is likely related to a selection bias because clinicians who are concerned that, either they may have given too much relaxant or have not had adequate time for the relaxant to wear off, may be more likely to apply a qualitative TOF monitor to attempt to assess depth of neuromuscular blockade and further reassure themselves that the patient is in a good position to be reversed with neostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, variants of SLCO1B1 were well demonstrated associated with reduced transport activity of OATP1B1, and variants of SLCO1A2 decreased transport activity towards the OATP1A2 substrate 28,29 . Moreover, rocuronium is a substrate for organic anion transporters (OATPs) 2,29 . Recently, a genome‐wide association study comprising 918 women undergoing surgery for breast cancer suggested that SLCO1A2 variation may alter uptake of rocuronium by OATP1A2 and was estimated to account for 4% of the variability in rocuronium dose 2 .…”
Section: Discussionmentioning
confidence: 99%
“…2,29 Recently, a genome-wide association study comprising 918 women undergoing surgery for breast cancer suggested that SLCO1A2 variation may alter uptake of rocuronium by OATP1A2 and was estimated to account for 4% of the variability in rocuronium dose. 2 Additionally, our results and those of Mei 8 indicate that OATP1B1 variants affect the clinical action of rocuronium. However, Costa and colleagues suggested that patients genotyped as -A or AA for SLCO1A2-189_-188InsA showed a reduction of total clearance of rocuronium compared to patients genotyped as -/-(151.6 vs. 207.1 ml/min).…”
Section: Slco1b1 and Slco1a2mentioning
confidence: 99%
See 2 more Smart Citations